Symbolic messages of Covid-19 poster art by Intan Munirah Hamzah from Sabah Art Gallery / Issarezal Ismail and Siti Humaini Said Ahmad @ Syed Ahmad - Ismail, Issarezal; Said Ahmad @ Syed Ahmad, Siti Humaini (2021)
A poster is not just a combination of visual and text that have aspects of beauty or entertainment. However, it is a tool or medium of non-verbal communication created by its creator to convey something in the form of messages to others. This study seeks to approach, understand and explain the message of a series of posters of Covid-19 from the Sabah Art Gallery created by Intan Munirah Hamzah covering the structure, content, and function of its message. The art study approach, which is fundamentally based on a qualitative approach that emphasizes a descriptive and holistic explanatory system, has been used at the same time through a conceptual framework built on relevant concepts as a frame of analysis. The analysis shows that the Covid-19 poster from the Sabah Art Gallery are trying to convey the message of self-safety and prevention related to the Covid-19 phenomenon that is plaguing the world today. Its message structure conveys the meanings of courtesy and morality, compliance, and even discretion when everyone is required to practice some safety and precautionary measures such as wearing a facemask, sitting at home, and frequently washing their hands. This series of poster not only plays its role in providing information and preventive measures in the face of the Covid-19 phenomenon but also activates its function through teaching values such as health values, hygiene values, sacrifice values, and new social norms values in order to ultimately encouraging or inviting people to play their part in response to this global pandemic situation